AI and emerging technologies: revolutionising education - Mohd Nasir, Hazira; Musa, Aini Hayati; Mohd Zaid, Noor Azila; Mohd Nasir, Nadia (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
The traditional classroom model teachers lecturing at the front, students in rows, and a one-size-fits-all curriculum has remained largely unchanged for centuries, yet it no longer meets the diverse needs of modern learners. With wide variations in learning styles, abilities, and interests, even dedicated teachers struggle to personalise instruction for large groups, while administrative burdens pull them away from meaningful mentoring. At the same time, today’s world requires skills like creativity, critical thinking, and digital literacy that standardised, memorisation-based systems often fail to cultivate. These pressures make educational transformation essential, and emerging technologies, especially AI, offer the potential for personalised, immersive, and human-centred learning.